PENERAPAN METODE TALKING STICK DAN REFLEKTIF DAPAT MENINGKATKAN HASIL BELAJAR SISWA PADA MAPEL PAI DI SMP AL-HUSNA KELAS VIII - Nafees, Wildan; Santi Lisnawati; Putri Ria Angelina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The learning outcomes of students at Al-Husna Pabuaran Middle School have not achieved the expected results, especially in the subject of Islamic Religious Education.  This study aims to explain the application of the Talking stick learning method combined with the re-flective method and measure the increase in student learning outcomes in the subject of Islamic Religious Education (PAI) in class VIII of SMP Al-Husna Pabuaran. The reason for conducting this research is due to the low learning outcomes of students, the learning method is still centered on the teacher (lecture). This study uses the Classroom Action Re-search (CAR) method of the Kemmis and McTaggart model which was carried out for two cycles. 22 students of class VIII of the 2025/2026 academic year were the targets of this research. Data were collected through field observations, oral and written tests, interviews, and documentation. The results of the study had a significant impact, the average class score increased from 69.5 (pre-cycle) to 74.9 (Cycle I) and 79.6 (Cycle II). The percentage of learning completion increased from 27.2% (Pre-cycle) to 36.3% in Cycle I and 81.8% in Cycle II, exceeding the minimum completion criteria value of 75. It can be said that the application of the Talking stick and reflective methods has proven effective in improving the Logic, Ethics, and Character of students for this Islamic Religious Education learning.